ANALISIS BAMBU SEBAGAI STRUKTUR LANTAI BANGUNAN RUMAH TINGGAL BERTINGKAT - Aditya Purnama (JURNAL DAKTILITAS, 2021)
Abstract Natural product renewable that can be obtained easily, cheaply, easily planted, grows fast, can reduce the effects of global warming, and has a very high tensile strength that can becompeted with steel. Bamboo is a material that is commonly found in several villages andmountainous areas in Tulungagung, therefore bamboo material has a relatively cheap price.Loading reviews dead load and lives load. The analysis carried out in this study isloading, calculating the ultimate moment, calculating the capacity of one bamboo, thencalculating the number of bamboo needs that must be installed, and calculating the installationdistance of bamboo. Then to determine the stress and deflection of the bamboo floor structure,3D analysis using Midas Gen 2019.Based on the results of the analysis with a stretch of 4.5m x 4m bamboo floor structure,8 pieces of bamboo are needed in the X direction and 9 pieces in the Y direction. with abamboo distance of 50 cm. The maximum deflection based on the analysis results is 6.39 cm,while the stress in the X direction is 65.3 MPa and the Y direction is 53.8 MPa.Keywords: Bamboo; renewable; analysis; stress; deflection AbstrakMaterial bambu merupakan produk hasil alam yang renewable yang dapat diperolehdengan mudah, murah, mudah ditanam, pertumbuhan cepat, dapat mereduksi efek globalwarming serta memiliki kuat tarik sangat tinggi yang dapat dipersaingkan dengan baja. Bambumerupakan material yang banyak ditemui di beberapa desa dan daerah pegunungan diTulungagung, maka dari itu material bambu memiliki harga yang relatif murah.Pembebanan meninjau beban mati dan beban hidup. Analisis yang dilakukan padapenelitian ini adalah pembebanan, menghitung momen ultimate, menghitung kapasitas satubuah bambu, kemudian menghitung jumlah kebutuhan bambu yang harus dipasang danmenghitung jarak pemasangan bambu. Kemudian untuk mengetahui tegangan dan lendutandari struktur lantai bambu tersebut digunakan anaisis 3D dengan menggunakan Midas Gen2019.Berdasarkan hasil dari analisis dengan bentangan struktur lantai bambu 4,5 m x 4 m,diperlukan bambu pada arah X sebanyak 8 buah dan arah Y sebanyak 9 buah dengan jarakbambu 50 cm. Lendutan maksium berdasarkan hasil analisis sebesar 6,39 cm, sedagnkanteganagan arah X 65,3 MPa dan arah Y 53,8 MPa.Kata Kunci: Bambu; renewable; analisis; tegangan; lendutan